STRATEGI STUDI DESKRIPTIF GURU PADA PEMBELAJARAN BAHASA INGGRIS DI KELAS V MADRASAH IBTIDAIYAH STUDI KASUS DI MI MIFTAHUL ULUM MATARAM UDIK - Elvandari Maulana; Septa Asri Anisatussariroh; Asti Maharani; Nirmala Nirmala; Bella Arum Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
English learning in Madrasah Ibtidaiyah still faces various challenges, particularly related to limited media, teaching strategies, and students’ readiness to comprehend a foreign language. This study aims to describe the descriptive study strategies applied by the teacher in English learning for fifth-grade students at MI Miftahul Ulum Mataram Udik. This research employed a qualitative approach with a descriptive study design. The subject of the study was the English teacher of grade V and several students as supporting informants, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the interactive model of Miles & Huberman consisting of data reduction, data display, and conclusion drawing. The findings reveal that the teacher implemented three main strategies: the use of simple visual media (pictures, flashcards, and interactive whiteboard), the application of communicative methods through simple conversations, and the provision of descriptive feedback to correct students’ errors constructively. The teacher stated that visual media helped students understand vocabulary more easily, while students admitted that they became more confident in speaking English through simple dialogue practices. Moreover, descriptive feedback encouraged students to correct their mistakes and increased their learning motivation. This study concludes that descriptive study strategies enable teachers to reflect on their teaching practices while improving the quality of English learning in madrasah. The findings contribute to enriching the literature on English teaching for young learners and serve as practical references for teachers in developing teaching strategies suitable for the characteristics of MI students.